Live as African : On the Relevance of Thomas Sankara’s Agenda for Economic Liberation - Sylla, Ndongo Samba; Institute of African Studies (University of Bayreuth African Studies Working Papers, 2022)
"We must accept to live as African – that is the only way to live free and dignified", said the late Thomas Sankara in his famous 1987 speech at the Organization of African Unity. "Live as African", beyond summarizing Sankara's political and ethical vision, draws an agenda for economic liberation articulated around the ideal of self-sufficiency understood both as freedom from external domination and as capacity to self-determination through reliance first and foremost on one’s own resources. In this article, I argue that this agenda is the only one sustainable both for African peoples and for the Planet once it is realized that peoples from the periphery as a whole will never be able to achieve the same consumption/waste levels as peoples in the center, as global South thinkers Celso Furtado and Samir Amin demonstrated some decades ago. Since then, a growing literature has shown why the Western development “model”, due to its ecological exceptionalism, is simply not reproducible elsewhere and why the promise of economic catch-up is illusory. Building on these findings and on the importance and implications of monetary sovereignty, I will elaborate on the principles of a Sankara-inspired economic model that could deliver a free and dignified life to all.
Keywords: Economic development; Delinking; External Debt; Unequal Ecological Exchange; Monetary Sovereignty Développement Economique; Déconnexion; Dette Extérieure; Echange Ecologique Inégal; Souveraineté Monétaire